A CASH BUDGET FOR THE SMALL MANUFACTURER. - Wasley, Robert S. (The Accounting Review, 1954)
Abstract The cash budget is probably the most basic of all budgets for the small manufacturer. The cash budget can serve a multitude of purposes. It not only can help to assure adequate cash resources but also it can serve as a sort of expense budget of the business. In this way, several budgets have been rolled into one.